Detection of deletion and mutation on pig Mx1 gene (gene resistance to influenza virus) with PCR-RFLP Nar I restriction - Sumantri, Cece; Morzumi, T; Hamashima, N (Indonesian Journal of Animal and Veterinary Sciences, 2001)
The study was done to detect the incident of deletion and mutation in exon 14th of Mx1 gene in pig. Six hundred base pairs at the position (1937 to 2537) of the 14th exon of the pig Mx1 gene was amplified by polymerase chain reaction (PCR) from 15 breed of pig DNA sample. The amplified PCR products were digested by Nar I enzyme that called restriction fragment length polymorphism (PCR-RFLP) technique. The results show genetic polymorphism at the 14th exon of pig Mx1 gene. The Nar I digested revealed three phenotyphic variation (C/C, C/N and N/N, designated for Nar I cut homozygote, heterozygote and for Nar I no cut homozygote, respectively). The Nar I (N/N or C/N) type is corresponding to (1) the deletion 11 bp at the position 2064 to 2075. This type was observed in Landrace breed. (2) the incidence of two point mutation at the position 2065 Guanine (G) change to Thymine (T) and at the position 2124 Guanine (G) change to Adenine (A).This type was observed in Chinese native pig (Meishan) and Vietnamese native pig. Â  Key words: Deletion, mutation, pig Mx1 gene and PCR-RFLP